2019
DOI: 10.1177/1468087419893897
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the roundness of deformed cylinder liner in internal combustion engines by using a non-circular liner profile

Abstract: Increasing the efficiency of internal combustion engines is of major interest for reduced greenhouse gas emission. A significant improvement potential is given with the reduction of friction losses. Here, especially the friction between the piston ring and the cylinder liner is of interest. This article describes a study with the target to enhance the piston ring–cylinder liner conformation through increasing the roundness of the deformed liner during the warm operation state. The approach is based on the assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…Both the trends and the values of the deformations have good agreement with experimental data described by the authors of [25]. The detailed model configuration, boundary conditions, temperature distributions, mesh properties, grid independence test, circumferential position dependent deformation, and model validation have been explained by the authors of [14].…”
Section: Physical and Computational Modelsupporting
confidence: 74%
See 4 more Smart Citations
“…Both the trends and the values of the deformations have good agreement with experimental data described by the authors of [25]. The detailed model configuration, boundary conditions, temperature distributions, mesh properties, grid independence test, circumferential position dependent deformation, and model validation have been explained by the authors of [14].…”
Section: Physical and Computational Modelsupporting
confidence: 74%
“…Commonly, the cross section has a circular form. In a preceding work [14], it was shown that an elliptical liner cross section in the cold state can reduce the roundness error in the fired state by more than 75% for the terminal cylinder in four-cylinder gasoline engine due to the inhomogeneous thermal conditions. It was found that the deformation of a circular liner leads to a nearly elliptical shape in the fired state, while an initially elliptic liner with opposite ellipticity in the cold state deforms to an almost circular shape in the fired state.…”
Section: Conical Linersmentioning
confidence: 99%
See 3 more Smart Citations